2008
DOI: 10.1210/en.2007-1064
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Human Testicular Peritubular Cells: Identification of Secretory Products and Regulation by Tumor Necrosis Factor-α

Abstract: Testicular peritubular cells are myofibroblastic cells, which represent the major cellular components of the wall of the seminiferous tubules. In men their phenotypic characteristics, including possible secretory activity and regulation, are not well known, in neither normal nor pathologically altered testes. Especially in testes of men with impaired spermatogenesis, the cytoarchitecture of the tubular wall is frequently remodeled and presents fibrotic thickening, increased innervation, and infiltration by mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 55 publications
7
93
0
1
Order By: Relevance
“…Our TNF-a and a-SMA immunostaining and ELISA experiments revealed that other cell types release this cytokine in normal testicular processes as previously described (Suominen et al, 2004;Schell et al, 2008), pointing that our PTCs cultures could contain residual contaminations with other cell populations from the interstitial areas of the testes (i.e. immune cells).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our TNF-a and a-SMA immunostaining and ELISA experiments revealed that other cell types release this cytokine in normal testicular processes as previously described (Suominen et al, 2004;Schell et al, 2008), pointing that our PTCs cultures could contain residual contaminations with other cell populations from the interstitial areas of the testes (i.e. immune cells).…”
Section: Discussionsupporting
confidence: 79%
“…The effect of this cytokine on the regulation of human testicular PTC secretory activity and its involvement in impaired spermatogenesis has been reported (Schell et al, 2008). Additionally, this factor has been found to play a role in tumor stroma cross talk, causing the upregulation of MMP-9 (Stuelten et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Similar inflammatory molecules are important in regulating the blood-testis barrier, which affects the function of Sertoli cells. Tumor necrosis factor-alpha, transforming growth factor-β3 (40), and interleukin-1 can disturb blood-testis barrier dynamics (41). Interleukin-6 alters blood-testis barrier function by inhibiting protein degradation (42).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to do so, our laboratory established a method to culture and study HTPCs. It is based on very small testicular tissue samples from adult patients with obstructive azoospermia but normal spermatogenesis (HTPCs) and non-obstructive azoospermia, impaired spermatogenesis, and testicular fibrosis (HTPCFs) (Albrecht et al 2006, Schell et al 2008, Spinnler et al 2010, Adam et al 2011.…”
Section: R108 a Mayerhofermentioning
confidence: 99%
“…They produce signaling factors, including interleukin 6 (IL6), monocyte chemotactic protein 1 (MCP1), nerve growth factor (NGF), and its precursor proNGF, as well as glial cell line-derived neurotropic factor (GDNF). Cyclooxygenase-2 (COX2) was detected upon TNFa treatment and prostaglandins, especially PGD2, and metabolites may also be among the produced factors (Schell et al 2008, Spinnler et al 2010. The cells express several antioxidant proteins, namely catalase, parkinin/DJ-1, peroxiredoxin 1, superoxide dismutases (SOD) 1 and 2, glutathione-S-transferase, and heme oxygenase (HMOX1) (Kampfer et al 2012).…”
Section: Recent Insights Into the Nature Of Human Peritubular Cellsmentioning
confidence: 99%